DIVERSITY OF FISH CAUGHT IN THE BATANG JULU SOLOK SELATAN - Wati, Gita Seftia; Nurhadi, Nurhadi; Fitriani, Vivi (BioCONCETTA, 2023)
The fish species in the Batang Julu are still fairly numerous but have not been recorded accurately. This study aims to determine the diversity of fish species caught in the Batang Julu. The method used in this research is a descriptive survey. Samples were taken at places where people searched for fish using nets, fishing rods, arrows and traps. Sampling started from February 10-24, 2023. Sampling was done in the morning at 07.00-11.00 and in the afternoon at 15.00-18.00. Samples were identified at the Zoology Laboratory of PGRI University of West Sumatra by observing fin color, body color, and morphometric measurements using the identification guidebook of Kottelat and Whitten (1993), and Saanin (1984). The results showed that there were 8 fish species consisting of 8 Genus, 4 Families, and 4 Orders caught in the Batang Julu. The diversity of fish species in the Batang Julu South Solok is classified as moderate with a diversity index of 2.059 measured using the Shanon-Wiener formula.